Arbitrary long digit integer sorter HW/SW co-design - Cheng, Shun-Wen (Proceedings of the 2003 Asia and South Pacific Design Automation Conference, 2003)
The coming of multimedia era and information security era indicates that must process longer digit integer data. Previous sort researches focus on pure performance of large amount of finite fixed digit/bit number. This paper discusses on effectively solving arbitrary long digit integer sorting problem by HW/SW co-design under the Area x Time2 (AT2) price-performance constraint. The work proposes multi-level (two-level) sort architecture to attain the object: an accomplished fixed-digit (k-bit) hardware sorter implements the first or basic level sorting, software programmed radix 2k sort implements the second or higher level sorting. By Super Radix Sorting HW/SW co-design and reuse techniques, the work makes fixed-digit HW sorters more flexible and useful.